Черноводье: [роман : 12+] / Валентин Решетько - Решетько Валентин Михайлович (Сибириада, 2014)
Экземпляры: ф.11 (20151007) / Инвентарный номер: 059556 / Цена: 229.00 / Авт.знак: Р 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6